2020
DOI: 10.1038/s41418-020-00656-0
|View full text |Cite
|
Sign up to set email alerts
|

CRSP8 promotes thyroid cancer progression by antagonizing IKKα-induced cell differentiation

Abstract: CRSP8 plays an important role in recruiting mediators to genes through direct interaction with various DNA-bound transactivators. In this study, we uncovered the unique function of CRSP8 in suppressing thyroid cancer differentiation and promoting thyroid cancer progression via targeting IKKα signaling. CRSP8 was highly expressed in human thyroid cancer cells and tissues, especially in anaplastic thyroid cancer (ATC). Knockdown of CRSP8 suppressed cell growth, migration, invasion, stemness, and induced apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…[14][15][16]37 In our previous studies, for the first time, we successively reported the tumor-promoting role of MED27 in melanoma and thyroid cancer by activating the NF-κB/iNOS signaling pathways and antagonizing IKKα-induced cell differentiation, respectively. 13,38 Of note, in terms of the function of MED27 in breast cancer, although a recent report found that MED27 promoted the malignant behavior of cells by affecting Sp1 in breast cancer, 16 its effects were mainly explored for the proliferation and apoptosis of breast cancer cells. As for its role in maintaining breast cancer cell metastasis and stemness and the responsible molecular mechanisms, these points have been relatively unexplored.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[14][15][16]37 In our previous studies, for the first time, we successively reported the tumor-promoting role of MED27 in melanoma and thyroid cancer by activating the NF-κB/iNOS signaling pathways and antagonizing IKKα-induced cell differentiation, respectively. 13,38 Of note, in terms of the function of MED27 in breast cancer, although a recent report found that MED27 promoted the malignant behavior of cells by affecting Sp1 in breast cancer, 16 its effects were mainly explored for the proliferation and apoptosis of breast cancer cells. As for its role in maintaining breast cancer cell metastasis and stemness and the responsible molecular mechanisms, these points have been relatively unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Reports regarding the function and the corresponding molecular mechanism of MED27 in tumorigenesis and development are still few. Our previous studies demonstrated the tumor‐promoting role of MED27 in melanoma survival and its dedifferentiation function in thyroid cancer progression 13 . It has also been reported to promote the proliferation and metastasis of adrenal cortical carcinoma cells by affecting the EMT process 14 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Over the past few decades, thyroid cancer has become an increasingly significant public health issue in most regions of the world [29]. Among thyroid cancers, ATC is a highly lethal cancer, for which treatment strategies have not yet been universally acknowledged, nor is there identified any highly effective treatment option [30]. Hence, the determination of effective treatment agents targeting ATC as well as the discovery of relevant original therapeutic mechanisms are essential to improving the prognosis of ATC patients.…”
Section: Discussionmentioning
confidence: 99%
“… 9 An increasing number of studies have demonstrated that EMT activation is closely related to multiple milestones in the development of cancer, including distant metastasis, extrathyroidal extension, and increased cancer cell stemness, and can be observed at the tumor‐stromal boundary of TC. 10 , 11 Due to the complicated process of EMT, which involves various transcriptional and translational factors associated with TC, ancillary diagnostic tools based on standardized genomic characteristics would offer better predictive value than risk stratification based on clinical parameters alone. 12 , 13 Based on the pivotal role of EMT in PTC invasion and anaplastic transformation, we established a novel 10‐gene signature derived from prognosis‐related differentially expressed EMT‐related genes (DE‐ERGs) using Cox proportional hazard analysis.…”
Section: Introductionmentioning
confidence: 99%